Effect of heat stress on milk production and its composition of Holstein Friesian crossbred dairy cows (Asian Journal of Medical and Biological Research, 2016)
The aim of this research was to observe the effect of heat stress on milk yield and milk compositions of Holstein Friesian crossbred (HF) dairy cows. To fulfill the objectives, a total of 9 Holstein Friesian crossbred cows were selected for this study. Green grasses (German, Para) were supplied adlibitum and concentrate feeds (mixture of wheat bran, rice polish, mustard oil cake, di-calcium phosphate and salt) were supplied at the rate of 2.0 kg/day/cow. Management practices for all the cows were similar following the BAU Dairy farm practices. Data were collected on milk yield (l/h/d), relative humidity (%) and barn temperature (0C). The obtained temperature humidity index (THI) of July, August, September and October were 84.95, 81.99, 81.40 and 79.57, respectively. The highest THI was found in July which indicated higher heat stress during this month. A significant difference (p